STRATEGIC FINANCIAL MANAGEMENT: TEMASEK HOLDINGS AS DANANTARA’S BENCHMARK FOR BUILDING NATIONAL WEALTH AND SUSTAINABLE DEVELOPMENT - Sazly, Syukron; Erri, Dirgahayu; Tambunan, Diana; Herlan, Hasta (Universitas Muhammadiyah Tangerang, 2025)
This study highlights the urgency of strategic and sustainable national wealth management through the establishment of Danantara, Indonesia’s sovereign wealth fund that adopts the successful model of Temasek Holdings in Singapore, yet operates within a more complex national economic and political context. The purpose of this research is to analyze Danantara’s strategic factors using the SWOT approach, formulate strategies based on the TOWS matrix, and provide policy recommendations aligned with the Indonesia Emas 2045 vision. The research employs a qualitative analysis through a comparative study, literature review, and examination of official documents. The findings reveal Danantara’s strengths in asset scale and political support but weaknesses in governance and operational capacity. The study’s contribution and novelty lie in formulating portfolio separation strategies, strengthening independent governance, and focusing investments in digital sectors, green energy, and global partnerships.